FORMING A SENSE OF RESPECT IN STUDENTS - Sulaymonbekov, Oybek (Журнал иностранных языков и лингвистики, 2022)
The successful mastering of socio-legal norms by them is of special importance in order to make students become active participants in the process of social relations. It is known that interaction between people is organized on the basis of certain social and legal norms. Personal life takes place directly in society, among the people who live in it.